Engineering the Effector Domain of the Artificial Transcription Factor to Improve Cellulase Production by Trichoderma reesei - Meng, Qing-Shan; Zhang, Fei; Wang, Wei; Liu, Chen-Guang; Zhao, Xin-Qing; Bai, Feng-Wu (Frontiers in Bioengineering and Biotechnology, 2020)
Filamentous fungal strains of Trichoderma reesei have been widely used for cellulase production, and great effort has been devoted to enhancing their cellulase titers for the economic biorefinery of lignocellulosic biomass. In our previous studies, artificial zinc finger proteins (AZFPs) with the Gal4 effector domain were used to enhance cellulase biosynthesis in T. reesei, and it is of great interest to modify the AZFPs to further improve cellulase production. In this study, the endogenous activation domain from the transcription activator Xyr1 was used to replace the activation domain of Gal4 of the AZFP to explore impact on cellulase production. The cellulase producer T. reesei TU-6 was used as a host strain, and the engineered strains containing the Xyr1 and the Gal4 activation domains were named as T. reesei QS2 and T. reesei QS1, respectively. Compared to T. reesei QS1, activities of filter paper and endoglucanases in crude cellulase produced by T. reesei QS2 increased 24.6 and 50.4%, respectively. Real-time qPCR analysis also revealed significant up-regulation of major genes encoding cellulase in T. reesei QS2. Furthermore, the biomass hydrolytic performance of the cellulase was evaluated, and 83.8 and 97.9% more glucose was released during the hydrolysis of pretreated corn stover using crude enzyme produced by T. reesei QS2, when compared to the hydrolysis with cellulase produced by T. reesei QS1 and the parent strain T. reesei TU-6. As a result, we proved that the effector domain in the AZFPs can be optimized to construct more effective artificial transcription factors for engineering T. reesei to improve its cellulase production.